2011
DOI: 10.1371/journal.pone.0021816
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 17A Promotes Hepatocellular Carcinoma Metastasis via NF-kB Induced Matrix Metalloproteinases 2 and 9 Expression

Abstract: Background IL-17A is a pro-inflammatory cytokine that plays important role in inflammatory disease pathology and tumor microenvironment. The aim of this study is to investigate the effect of IL-17A on the progression of hepatocellular carcinoma (HCC).Methodology and Principal FindingExpression pattern of IL-17A in clinical HCC samples (n = 43) was determined by immunohistochemistry staining. Transcript levels of MMP2, MMP9 and IL-17A were measured in another 50 pairs (including tumor and related non-tumor tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
174
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(183 citation statements)
references
References 44 publications
8
174
1
Order By: Relevance
“…A recent study also found that high expression of IL-17 and IL-17RE associated with poor prognosis of hepatocellular carcinoma (28). IL-17A has also been found to promote hepatocellular carcinoma metastasis via MMP2 and 9 expression (29).…”
Section: Discussionmentioning
confidence: 89%
“…A recent study also found that high expression of IL-17 and IL-17RE associated with poor prognosis of hepatocellular carcinoma (28). IL-17A has also been found to promote hepatocellular carcinoma metastasis via MMP2 and 9 expression (29).…”
Section: Discussionmentioning
confidence: 89%
“…Recent studies have shown that IL-17A stimulates tumor progression and metastasis in several tumor types (36)(37)(38). Although most CT-26 cells contain IL-17A receptor a (IL-17RA; ref.…”
Section: Il-17a Promotes Intravasation Of Cancer Cellsmentioning
confidence: 99%
“…IL-17 enhances MMP-9 expression and lung tumor cell motility. IL-17 can stimulate expression of MMP-9 (1,18,36), and this may partially account for the selective stimulation of lung tumor growth in vivo. Consequently, we evaluated gelatinase activity in the BAL fluid from adenovirus-treated mice by zymography.…”
Section: Il-17 Overexpression Increases Lung Tumor Growth In K-mentioning
confidence: 99%